PRAKTEK PENEGAKAN HUKUM OLEH POLDA SUMSEL DALAM MENANGANI KASUS PENCURIAN DENGAN KEKERASAAN - antoni antoni; anjeli anjeli (Tazir, 2023)
"Law Enforcement Practices by the South Sumatra Regional Police in handling cases of theft with violence". Theft with violence is a crime that is prohibited in Indonesian law as well as in Islamic law. The formulation of the problem raised in this study is how law enforcement is carried out by the South Sumatra Regional Police against perpetrators of criminal acts of theft with violence, and how is the review of Islamic Criminal Law on law enforcement carried out by the Regional Police of South Sumatra against perpetrators of criminal acts of theft with violence . he purpose of this study is to determine law enforcement carried out by the South Sumatra Regional Police against perpetrators of criminal acts of theft with violence, as well as to find out the review of Islamic Criminal Law on law enforcement carried out by the Regional Police of South Sumatra against perpetrators of criminal acts of theft with violence. The method used in this research is empirical juridical research method, empirical juridical research is field research by observing what happens in the field. As for the results of this study, it can be seen that law enforcement is carried out by the Regional Police of South Sumatra against criminal acts of theft with violence, namely in 2 ways, namely preventive efforts with the aim of preventing the occurrence of a crime and repressive efforts, namely a form of action or disclosure of cases against the perpetrators. criminal acts related to theft with violence. As for the review of Islamic Criminal Law on law enforcement carried out by the Regional Police South Sumatra, namely by being subject to sanctions in the form of cutting off hands, being killed or crucified or exiled from their place of residence, according to their actions. Keywords: Law Enforcement, Theft with Violence, South Sumatra Regional Police.